Anatomical Features of the Scots Pine Stem Phloem After Forest FireAnatomical Features of the Scots Pine Stem Phloem After Forest Fire - V. V. Stasova; O. N. Zubareva; G. A. Ivanova (Russian Academy of Sciences, Siberian Branch Publishing House, 2015)
The aim of this work was to study changes in anatomical structure of phloem tissue in pine (Pinus sylvestris L.) stems influenced by creeping forest fires of various rates. The experiments were carried out in the Lower Angara river region of the Angara provenance, Krasnoyarsk Krai, Central Siberia. The trees with green crowns and different fire damaged butts were chosen as models. Control (undamaged) trees were taken from stands adjacent to experimental plots. The changes of inner bark thickness, number of phloem annual layers between cambium and periderm and number of cells in conductive phloem were found in the stem side opposite to fire scars. The structure fluctuations of phloem tissue were detected: disturbances of sieve cell arrangement, phloem ray enlargements, resin canal overgrowth and formation of great resin ducts. The lignin accumulation was observed in inner bark and a large amount of callusing was detected between conductive and nonconductive phloem. Over the course of time, repairing of tissues occurred and the normal inner bark structure and chemistry (without lignin) were restored. The creeping fire of low intensity caused the maximal changes of phloem quantitative characteristics in trees with bark charring and these tendencies were stored after eight years. After creeping fire of high intensity the tendency for phloem thickening in trees with one fire scar and to thinning in strongly damaged trees were revealed. Also tendencies to decrease of the number of phloem annual layers, number of sieve cells in conductive phloem and ray frequency with increasing of stem injury degree were observed, besides axial parenchyma percentage trended to increase. Eight years after fire these tendencies were often not visible.